PENGARUH INFLASI, NILAI TUKAR DAN SUKU BUNGA SBI TERHADAP VOLATILITAS HARGA SAHAM (Studi Pada Perusahaan Yang Terdaftar Dalam Indeks LQ45 Periode 2008-2012) Maslan - B11111093, MASLAN (Jurnal Manajemen Update, 2015)
The purpose of this study is to determine the effect of inflation, exchange rates and interest rates SBI to stock price volatility companies listed on LQ45 period 2008-2012. The data used in this research is secondary data, while the sampling technique used purposive sampling. The sample in this study amounted to 13 companies that made it into the sample and the exact criteria listed in LQ45 index during the study period. The analysis technique used is multiple regression analysis and hypothesis testing using t test partial and coefficient of determination. From the results of the analysis showed that the three partially independent variables, namely inflation, exchange rates and interest rates SBI and significant positive effect on the stock price volatility with a significance level a = 5%. Predictive ability or the effect of these three variables to the volatility of the stock price is equal to 83.9% as at the show by the value of R Square of 0.839, while the rest influenced by other factors not included in the research model. Â  Keywords: Volatility Stock Prices, Inflation, Exchange Rate and Interest Rate Bank Indonesia certificates.